The trouble with maths : a practical guide to helping learners with numeracy difficulties - Chinn, Stephen J., author (Milton Park, Abingdon, Oxon ; New York : Routledge, 2012)
"Now in a second edition, the award-winning The Trouble with Maths offers important insights into the often confusing world of numeracy. By looking at learning difficulties in maths from several perspectives, including the language of mathematics, thinking styles and the demands of individual topics, this book offers a complete overview of the most common problems associated with mathematics teaching and learning. It draws on tried-and-tested methods based on research and the author's many years of classroom experience to provide an authoritative yet highly accessible one-stop classroom resource. Combining advice, guidance and practical activities, this user-friendly guide will enable you to: develop flexible thinking skills; use alternative strategies for pupils to access basic facts; understand the implications of pre-requisite skills, such as working memory, on learning; implement effective preventative measures before disaffection sets in; recognise maths anxiety and tackle self-esteem problems; tackle the difficulties with word problems that many pupils may have; select appropriate materials to enhance understanding. With useful features such as checklists for the evaluation of books, an outline for setting up an inclusive Maths Department policy and a brand new chapter on materials, manipulatives and communication, this book will equip you with the essential skills to tackle your pupils' maths difficulties and improve standards. This book will be useful for all teachers, classroom assistants, learning support assistants and parents who have pupils that underachieve with maths"--